The protection of pregnant adolescents in Malaysia : towards a legal framework - Aishah Mohd Nor (Ahmad Ibrahim Kulliyyah of Laws, International Islamic University Malaysia, 2020)
This study investigates the existing legal framework for the protection of adolescent pregnancies in the context of education, family law, criminal law and protection against sexual crimes in Malaysia with adherence to the international treaties of the United Nations Convention on the Rights of Children (UNCRC) and the United Nations Convention on the Elimination of All Forms of Discrimination Against Women (CEDAW) and within the principles of the Islamic law (maqasid al-Shariah). This study further examines the role of the government departments, non-government agencies as well as social activists in implementing the laws and policies as well as the effectiveness of the efforts in contemplating the contemporary needs of pregnant adolescents in Malaysia. This study utilises a mixed qualitative approach comprising of two methodologies; firstly, library research of the existing laws, treaties, reports, studies and other information pertaining to adolescent welfare and protection systems in the international treaties, also, analysing Malaysia's responses to the treaties within the purview of the Islamic laws. This data constitutes the primary data for this research. Secondly, fieldwork interviews with the government departments, non-government agencies as well as social activists as enforcement agents dealing directly with pregnant adolescents. Critical analysis was applied to understand the multitude problem on-the-ground and the consideration of the pregnant adolescent's best interests from the socio-legal approaches. This data constitutes the secondary data for this research. This study establishes the ongoing reforms in the domestic laws and policies in response to the ratification of UNCRC and CEDAW since 1995. The numerous efforts done by the government departments, non-government agencies and social activists prove the readiness and seriousness of the Malaysian authorities and society in strengthening the current protection and welfare system in Malaysia with regards to pregnant adolescents. Nonetheless, it was found that the absence of a legal framework which includes an adolescent pregnancy focused policy, a national strategic vision for the adolescent pregnancy welfare system and coordinated support services for pregnant adolescents; affects the smooth implementation of the currently existing laws and policies on this matter. Therefore, it is anticipated that a more legal framework and concerted services will help to promote a holistic approach to strengthen the welfare of pregnant adolescents and safeguard them from unnecessary harm.